Developing Learner Autonomy and Goal-Setting through Logbooks - Diane Raluy; Ramon Mislang (Studies in Self-Access Learning Journal)
From an earlier study undertaken by the researchers, data revealed that more than 90 percent of students thought making goals would help them achieve academic success in English. However, the lack of explicit instructions on goal setting in classrooms resulted in students making goals that were often too difficult to achieve. In addition, a system for helping students monitor and evaluate their goals through teacher and peer support appears to be absent in many educational contexts. To help students attain higher success with achieving goals, a system inspired by aspects of the GROW model (Whitmore, 2017) was created to support goal-setting activities. For 13 weeks, students drafted goals on Google docs and shared them with peers during classroom instruction. Classroom activities were implemented to help encourage peer support and exploration of goals inside the classroom. Outside of the classroom, Google docs provided a way for teachers to view students’ progress towards goals and a platform to offer advice and support where needed. Qualitative and quantitative data were collected from a pre-semester and post-semester survey. Results are intended to help advance methods for turning goal-setting tasks into an interactive feedback system. This system could play a valuable role in autonomous learning environments.